2019
DOI: 10.33448/rsd-v8i1.618
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho da alface Vanda em relação ao uso de adubo químico e composto orgânico

Abstract: The horticulture is very used in the familiar agriculture in the Brazil, Para state, in which the main part of production is used for family consumption. The lettuce more cultivated is Vanda (Lactuca sativa L.) and the family use own labor. The main objective this paper was evaluable the development of lettuce cv Vanda cultivated in beds with organic compounds and chemistry fertilization (NPK). The radicular system, plant height and production of mass fresh were evaluated. The best results in relation of roots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Veras et al (2019) observed that fertilization with mineral N-P-K produced higher fresh mass in lettuce plants (92 g/plant) than the treatment using organic compost (56 g/ plant). Similarly, the highest fresh mass of crispy head lettuce was 39 g/plant using 20 L of organic compost made with household solid residues (Silva et al, 2019). In studies using food residue compost in lettuce cultivation, Freitas et al (2018) observed higher shoot fresh mass (14 g/plant) using 100% of compost, when compared with different mixtures of soil and compost, showing that this type of residue has potential to be used in composting.…”
Section: Resultsmentioning
confidence: 99%
“…Veras et al (2019) observed that fertilization with mineral N-P-K produced higher fresh mass in lettuce plants (92 g/plant) than the treatment using organic compost (56 g/ plant). Similarly, the highest fresh mass of crispy head lettuce was 39 g/plant using 20 L of organic compost made with household solid residues (Silva et al, 2019). In studies using food residue compost in lettuce cultivation, Freitas et al (2018) observed higher shoot fresh mass (14 g/plant) using 100% of compost, when compared with different mixtures of soil and compost, showing that this type of residue has potential to be used in composting.…”
Section: Resultsmentioning
confidence: 99%
“…Isso pode estar relacionado a melhoria nas características físico-químicas no solo, pela disponibilidade de nutrientes causados pela adição desse condicionador de solo. Segundo Veras et al (2019), os composto orgânico Research, Society andDevelopment, v. 9, n. 11, e74091110375, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.10375 produzidos através do uso de casca de arroz carbonizada, serragem, esterco de gado, casca de cacau triturada e amendoim forrageiro resultou em um composto com potencial como condicionador de solos e fertilizante, fato este confirmado nos resultados obtidos quanto à análise do desenvolvimento da alface. Fonte: Autores (2019).…”
Section: Fator Condicionadorunclassified